2020
DOI: 10.1371/journal.pone.0227772
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, risk factors and healthcare costs of central line-associated nosocomial bloodstream infections in hematologic and oncologic patients

Abstract: Non-implanted central vascular catheters (CVC) are frequently required for therapy in hospitalized patients with hematological malignancies or solid tumors. However, CVCs may represent a source for bloodstream infections (central line-associated bloodstream infections, CLABSI) and, thus, may increase morbidity and mortality of these patients. A retrospective cohort study over 3 years was performed. Risk factors were determined and evaluated by a multivariable logistic regression analysis. Healthcare costs of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
78
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(87 citation statements)
references
References 37 publications
5
78
1
3
Order By: Relevance
“…However, we also found that the composition ratio of hospital acquired BSIs increased significantly annually (from 73.4-76.2%). This result was consistent with the increase in various hospital-acquired infections in recent years [16,17] , and the risk factors may be related to the risk factors for BSIs and (or) hospital-acquired infections reported in many previous studies, such as ICU admission, the older age of hospitalized patients (aging population), prolonged hospital stay, leukocytopenia, acute myeloid leukemia and (or) increased use of invasive procedures including central venous catheters (CVCs) [18][19][20] . However, more details of the risk factors require further statistical analysis of the decrease in hospital-acquired BSIs in our hospital.…”
Section: Discussionsupporting
confidence: 87%
“…However, we also found that the composition ratio of hospital acquired BSIs increased significantly annually (from 73.4-76.2%). This result was consistent with the increase in various hospital-acquired infections in recent years [16,17] , and the risk factors may be related to the risk factors for BSIs and (or) hospital-acquired infections reported in many previous studies, such as ICU admission, the older age of hospitalized patients (aging population), prolonged hospital stay, leukocytopenia, acute myeloid leukemia and (or) increased use of invasive procedures including central venous catheters (CVCs) [18][19][20] . However, more details of the risk factors require further statistical analysis of the decrease in hospital-acquired BSIs in our hospital.…”
Section: Discussionsupporting
confidence: 87%
“…Unsurprisingly, patients requiring more than one CVC are at higher risk of CRI [ 39 ]. Among cancer patients, patients with hematological malignancies are at higher risk for CRIs compared with patients with solid tumors and the risk of infection is higher in patients with aggressive hematological malignancy such as leukemia and high-grade lymphoma, compared with patients with less aggressive malignancies [ 5 , 40 42 ]. Neutropenia is a major independent risk factor for CRIs, and neutropenic patients with bloodstream infections are at higher risk of mortality compared with non-neutropenic patients [ 43 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…The frequency of resulting central line-associated bloodstream infections (CLABSIs) in cancer patients is estimated at 0.5-10 per 1000 CVC-days. The associated mortality ranges from 12 to 40% depending on several factors, including patient comorbidities, CVC type, and microorganism causing the infection [2,[5][6][7][8]. Importantly, up to 70% of all CRIs may be preventable with current evidence-based strategies [9].…”
Section: Introductionmentioning
confidence: 99%
“…Also, a potential relation of insertion site and catheter-related complications has been reported [ 3 , 4 ]. Catheter-related bloodstream infections (CRBSI) are one of the most important infection in those patients, causing up to almost half of all bloodstream infections (BSI), and incidence rates ranging from 10 to 18 per 1000 central venous catheter days [ 5 , 6 ]. Besides the clinical impact, CRBSI are associated with prolonged hospitalizations, significant morbidity and increased health-care costs [ 7 ].…”
Section: Introductionmentioning
confidence: 99%